JUSTIFICATION OF THE AREA OF APPLICATION OF THE CONTAINER-PLATFORM ACCORDING TO THE ETSNG CODE (Conferencea, 2022)
In the published state, an analysis is made of the classification of goods that can be transported on an innovative container platform